The Transcriptional Corepressor HOS15 Mediates Dark-Induced Leaf Senescence in Arabidopsis - Zareen, Shah; Ali, Akhtar; Lim, Chae Jin; Khan, Haris Ali; Park, Junghoon; Xu, Zheng-Yi; Yun, Dae-Jin (Frontiers in Plant Science, 2022)
Multiple endogenous and environmental signals regulate the intricate and highly complex processes driving leaf senescence in plants. A number of genes have been identified in a variety of plant species, including Arabidopsis, which influence leaf senescence. Previously, we have shown that HOS15 is a multifunctional protein that regulates several physiological processes, including plant growth and development under adverse environmental conditions. HOS15 has also been reported to form a chromatin remodeling complex with PWR and HDA9 and to regulate the chromatin structure of numerous genes. However, unlike PWR and HDA9, the involvement of HOS15 in leaf senescence is yet to be identified. Here, we report that HOS15, together with PWR and HDA9, promotes leaf senescence via transcriptional regulation of SAG12/29, senescence marker genes, and CAB1/RCBS1A, photosynthesis-related genes. The expression of ORE1, SAG12, and SAG29 was downregulated in hos15-2 plants, whereas the expression of photosynthesis-related genes, CAB1 and RCBS1A, was upregulated. HOS15 also promoted senescence through dark stress, as its mutation led to a much greener phenotype than that of the WT. Phenotypes of double and triple mutants of HOS15 with PWR and HDA9 produced phenotypes similar to those of a single hos15-2. In line with this observation, the expression levels of NPX1, APG9, and WRKY57 were significantly elevated in hos15-2 and hos15/pwr, hos15/hda9, and hos15/pwr/hda9 mutants compared to those in the WT. Surprisingly, the total H3 acetylation level decreased in age-dependent manner and under dark-stress in WT; however, it remained the same in hos15-2 plants regardless of dark stress, suggesting that dark-induced deacetylation requires functional HOS15. More interestingly, the promoters of APG9, NPX1, and WRKY57 were hyperacetylated in hos15-2 plants compared to those in WT plants. Our data reveal that HOS15 acts as a positive regulator and works in the same repressor complex with PWR and HDA9 to promote leaf senescence through aging and dark stress by repressing NPX1, APG9, and WRKY57 acetylation.